The Axiology Review of Short Story in Textbook toward the Character Empowerment for the Learners - Tri Lande; Suminto A Sayuti; Yuriska Dewi; Eka Rahayu Putri (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2023)
This research described the axiology of short stories in the Indonesian language textbook, written by Suherli et al., on eleventh graders at Senior High School toward the learners' character education empowerment. The data consisted of excerpts consisting of life values and becoming the learners' character empowerment. The researchers collected the data by reading, listening, noting, and literature study techniques. The researchers analyzed the data descriptively and qualitatively with semantics validity, interrater reliability, and intra-rater reliability tests. The results showed that the short stories contained the life values, such as cultural, moral, religious, aesthetic, and social values. The values are meaningful and could be the lesson to develop positive attitudes of the learners and empower the learners’ characters.